Curious erasures: the sexual in wartime sexual violence. Issue 3 (3rd July 2018) - Baaz, Maria Eriksson; Stern, Maria
ABSTRACT: Wartime sexual violence is especially egregious precisely because it is a sexual form of violence that causes particular harms. Yet, curiously, and in contrast to feminist theory on sexual violence more generally, the sexual has been erased from frames of understanding in dominant accounts of wartime rape. This article places the seeming certainty that "wartime rape is not about sex (it's about power/violence)" under critical scrutiny and poses questions about the stakes of the erasure of the sexual in explanations of conflict-related sexual violence. It argues that the particular urgency that accompanies this erasure reflects the workings of familiar distinctions between war and peace, as well as efforts to clearly recognize violence and separate it from sex. Erasing the sexual from accounts of wartime rape thus ultimately reinscribes the normal and the exceptional as separate, and reproduces a reductive notion of heterosexual masculine sex (in peacetime) that is ontologically different from the violence of war.